Pendidikan Kesehatan Tentang Manajemen Kesehatan Menstruasi Terhadap Pengetahuan dan Sikap Remaja Madrasah Tsanawiyah Swasta Amal Saleh - Nur Asnah Sitohang; Dewi Elizadiani Suza; Cut Adeya Adella (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2020)
Menstruation is periodic bleeding occurring repeatedly every month in women that starts about 14 days after ovulation and is released through the vagina. Menstruation is a characteristic feature of a woman's maturity where there is a change in the uterus in preparation for pregnancy. Menstrual health management (MHM) is a term that is often used in relation to cleanliness during menstruation. Menstrual health management includes facilities used during menstruation including clean water, soap used for bathing and cleaning all parts of the body as well as cleaning sanitary napkins that have been used. MHM is also related to the access they have to safe and comfortable facilities to dispose of used sanitary napkins. Young women must understand knowledge about menstruation and how to manage it appropriately without shame or fear. Health education is a form of independent nursing action to help clients, both individuals, groups and communities in overcoming their health problems through learning activities in which the nurse acts as a nurse educator. This study aims to increase students' knowledge and attitudes about menstrual health management by providing health education. The method used was to socialize activities to the school, identify the condition of menstrual health service facilities in schools such as bathrooms, clean water supply, provide educational media for menstrual health management in the form of videos, leaflets and modules; conduct health education about menstrual health management and post tests. The data analysis used was univariate. The number of samples was 36 people, namely grade VII students. The results of the study that the majority of respondents were 12 years (77.8%), had menstruation (58.3%), age at first menstruation was 11 years (52.3%), experienced menstrual pain (66.7%), information sources regarding: (1) hygiene during menstruation is the mother (38.5%), (2) sanitary napkins from TV commercials (25%), menstruation from mothers (45.5%), (3) types of sanitary napkins currently used modern sanitary napkins (65.9%), (4) the current brand of sanitary napkins from mothers (36.5%). The majority of knowledge adolescents category is 88.9% good and the attitude of the adolescents is 100% positive. Research proves that there are still students with sufficient knowledge (10.1%) and considering the importance of MHM as an effort to prevent infection in the female reproductive system and minimize the occurrence of cervical cancer in women in the future. Researchers suggest that schools include this topic in subject matter so that reproductive health can be maintained.